2021
DOI: 10.2196/30079
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model of Osteonecrosis of the Femoral Head After Femoral Neck Fracture: Machine Learning–Based Development and Validation Study

Abstract: Background The absolute number of femoral neck fractures (FNFs) is increasing; however, the prediction of traumatic femoral head necrosis remains difficult. Machine learning algorithms have the potential to be superior to traditional prediction methods for the prediction of traumatic femoral head necrosis. Objective The aim of this study is to use machine learning to construct a model for the analysis of risk factors and prediction of osteonecrosis of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…In the development and validation cohort, the concordance index was 0.96 and 0.94; and the discrimination slope was 0.51 and 0.47 [ 51 ]. Wang et al [ 52 ] proposed a six-variable XGBoost model by comparing different models, established by machine learning algorithms, in predicting ONFH after FNFs treated with internal fixation. They concluded that the six-variable XGBoost model with six predictors, including reduction quality, VAS score, Garden classification, operative time, cause of injury, and fracture location, could better predict the risk of ONFH.…”
Section: Resultsmentioning
confidence: 99%
“…In the development and validation cohort, the concordance index was 0.96 and 0.94; and the discrimination slope was 0.51 and 0.47 [ 51 ]. Wang et al [ 52 ] proposed a six-variable XGBoost model by comparing different models, established by machine learning algorithms, in predicting ONFH after FNFs treated with internal fixation. They concluded that the six-variable XGBoost model with six predictors, including reduction quality, VAS score, Garden classification, operative time, cause of injury, and fracture location, could better predict the risk of ONFH.…”
Section: Resultsmentioning
confidence: 99%
“…Pathophysiology and risk factors for these underlying mechanisms are partially overlapping but also differ. For example, the Garden classification is an important risk factor for avascular necrosis risk, but it does not necessarily predict the risk of screw cutout or implant loosening [ 20 , 21 , 52 , 53 ]. Ideally, subgroup analysis should have been performed to predict these specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Model performance was assessed on a validation set using AUC, accuracy, recall, specificity, F1-Scores and probability calibration curves (Moons et al, 2019). SHAP (Lundberg et al, 2020;Wang et al, 2021b) and LIME (Molnar, 2020) were used to explainably analyze the optimal model. All data analysis and construction were conducted using Python 3.10.9.…”
Section: Development Of Predictive Modelsmentioning
confidence: 99%